Persistence of Folly : On the Origins of German Dramatic Literature - Lande, Joel B. (Book collections on Project MUSE., 2018)
"Persistence of Folly revises the conventional literary-historical narrative of German theater (and literature) through the lens of the stage fool. Including original interpretations of Goethe's Faust (1808) and Kleist's Broken Jug (1811), this study considers how the stage fool was reworked and redeployed over two centuries, helping to create a German literature of world-historical rank"--Provided by publisher.